TINGKAT KEPUASAN DAN LOYALITAS IBU RUMAH TANGGA DALAM MENGONSUMSI MINYAK GORENG KEMASAN DI KOTA BANDAR LAMPUNG - Qorima, Riska Nurul; Prasmatiwi, Fembriarti Erry; Adawiyah, Rabiatul (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2014)
This research aims to analyze satisfaction level and loyalty housewifes inconsuming oil package, the factors influencing the level of satisfaction level and loyalty housewifes inconsuming oil package in Bandar Lampung City. This research used survey method to 53 households in Bandar Lampung City taken Simple Random Sampling. This research was conducted in the Sub-district of South Teluk Betung at Bumi Waras Village and Sub-district Kemiling at Beringin Raya selected purposive. The analysis used the analysis of customer satisfaction index, the analysis of switcher buyer, habitual buyer, satisfied buyer, liking the brand, and committed buyer and logit analysis . The results showed that the level of satisfaction housewifes was 76.40 %, the level of loyalty housewife with a value is 84.91 % buyer switcher, habitual buyers 81.13 %, 75.47 % satisfied buyer, liking the brand 69.8 % and 71.70% committed buyer. Factors that influence of satisfaction level and loyaty housewifes were education, income, mother age, family members and the location of purchase. Keywords: Cooking oil packaging, CSI, logit, loyalty, satisfaction